Characterization of Escherichia coli and other bacteria isolated from condemned broilers at a Danish abattoir - Alfifi, Ahmed; Christensen, Jens P.; Hounmanou, Yaovi Mahuton Gildas; Sandberg, Marianne; Dalsgaard, Anders (Frontiers in Microbiology, 2022)
Meat inspection is important to ensure food safety and protect public health. Visual inspection of slaughtered carcasses for pathological changes should be supported by bacteriological analysis to determine whether the entire carcass or parts of it should be condemned. The aim of this study was to determine the bacterial species present in different sample types from condemned broiler carcasses. Furthermore, we investigated the genetic characteristics, zoonotic potential, and relatedness of E. coli, the predominant bacterial species isolated from the carcasses. A total of 400 broiler carcasses condemned because of cellulitis (100), scratches (100), hepatitis (100), and healthy control carcasses (100) were selected. Samples of meat, pathological lesion, and bone marrow of each carcass were obtained for microbial analysis. From the analyzed samples, 469 bacterial isolates were recovered with E. coli accounting for 45.8%, followed by Aeromonas spp. (27.9%), in particular A. veronii. The highest rate of bacterial isolation was observed in carcasses condemned with cellulitis, whereas carcasses with hepatitis had the lowest rate of bacterial isolation. Forty-four E. coli isolates originating from different sample types were selected for whole genome sequencing. A clonal relationship was shown between E. coli from different sample types of the same carcass condemned with cellulitis and scratches. A major clade of E. coli was found in carcasses condemned with cellulitis with isolates containing mdf(A), tet(A), and blaTEM-1B genes that confer resistance to macrolides, tetracycline, and ampicillin, respectively. E. coli in this clade all belonged to ST117 and clustered with E. coli isolates previously collected from dead chickens and carcasses condemned due to cellulitis in Denmark, Finland, and the United Kingdom. Bacterial evaluation results of carcasses condemned with cellulitis, scratches (moderate to severe skin lesion), and acute hepatitis confirmed the need for total condemnation of carcasses with these pathological findings. A similar evaluation should be done for carcasses affected with chronic hepatitis, and minor scratches lesions.